Cost Estimation Analysis Based on Construction Management, Value Engineering, and Lean Six Sigma for Cost Efficiency Improvement in Coal Transportation Road Projects - Laksana, Priyogi Karta; Suroso, Agus (Eduvest - Journal of Universal Studies, 2025)
This study aims to evaluate the cost efficiency of the coal haul road improvement project in Muara Tuhup, Central Kalimantan, through the application of Construction Management, Value Engineering, and Lean Six Sigma. Quantitative and qualitative approaches are used to analyze cost efficiency and technical aspects, with data collected through observations, interviews, and questionnaires. The results show that the three independent variables contribute 71.2% to cost efficiency, with Value Engineering being the dominant factor at 32.3%. The analysis shows cost savings of Rp 592.375 billion, or 28.49% of the initial budget, through the application of chip seal layers to increase the life of the road. Post-Value Engineering cost estimates show a reduction in maintenance costs of up to 20 years, with a payback period of 8 years and 10 months. This study recommends the application of Value Engineering and Lean Six Sigma to improve the cost efficiency and sustainability of coal haulage projects.